Penggunaan Media Sosial Dalam Pembelajaran Sejarah Untuk Meningkatkan Kemampuan Berpikir kritis Siswa - M Arin Nurdiansyah; Usmaedi Usmaedi; Weny Widyawati Bastaman (Program Studi Pendidikan Sejarah, Universitas Setiabudhi Rangkasbitung, 2025)
This study aims to explore the use of social media as a medium for history learning to enhance students' critical thinking skills at SMAN 1 Banjarsari. The background of this research stems from students' low interest andparticipation in history subjects, which are often perceived as boring. The research employs a qualitative approach with descriptive methods. Data collection techniques include observation, interviews with teachers and students, and documentation. The findings reveal that social media platforms, especially YouTube and Instagram, have been effectively used as learning tools. Teachers integrate visual content such as historicaldocumentaries and infographics to boost students’interest in learning. Moreover, students show improvement in critical thinking skills through activities like creating historical content and analyzing digital materials. However, challenges such as limited internetaccess and content validity were noted. Overall, the use ofsocial media has proven to be a significant tool inenhancing students’ critical thinking in understanding historical material.